Solution-processed assembly of ultrathin transparent conductive cellulose nanopaper embedding AgNWs. Issue 32 (27th July 2015) - Song, Yuanyuan; Jiang, Yaoquan; Shi, Liyi; Cao, Shaomei; Feng, Xin; Miao, Miao; Fang, Jianhui
Abstract : Ultrathin, highly transparent conductive cellulose nanopaper embedding AgNW junctions with excellent mechanical flexibility was assembled using a pressured extrusion process. Abstract : Natural biomass based cellulose nanopaper is becoming a promising transparent substrate to supersede traditional petroleum based polymer films in realizing future flexible paper-electronics. Here, ultrathin, highly transparent, outstanding conductive hybrid nanopaper with excellent mechanical flexibility was synthesized by the assembly of nanofibrillated cellulose (NFC) and silver nanowires (AgNWs) using a pressured extrusion paper-making technique. The hybrid nanopaper with a thickness of 4.5 μm has a good combination of transparent conductive performance and mechanical stability using bamboo/hemp NFC and AgNWs cross-linked by hydroxypropylmethyl cellulose (HPMC). The heterogeneous fibrous structure of BNFC/HNFC/AgNWs endows a uniform distribution and an enhanced forward light scattering, resulting in high electrical conductivity and optical transmittance. The hybrid nanopaper with an optimal weight ratio of BNFC/HNFC to AgNWs shows outstanding synergistic properties with a transmittance of 86.41% at 550 nm and a sheet resistance of 1.90 ohm sq −1, equal to the electronic conductivity, which is about 500 S cm −1 . The BNFC/HNFC/AgNW hybrid nanopaper maintains a stable electrical conductivity after the peeling test and bending at 135° for 1000 cycles, indicating remarkably strong adhesion and mechanical flexibility. Of importance here is that the high-performance and low-cost hybrid nanopaper shows promising potential for electronics application in solar cells, flexible displays and other high-technology products.